Design and Synthesis of Novel Podophyllotoxins Hybrids and the Effects of Different Functional Groups on Cytotoxicity - Zhongtao Yang; Zitong Zhou; Xiai Luo; Xiaoling Luo; Hui Luo; Lianxiang Luo; Weiguang Yang (Molecules, 2021)
Development of novel anticancer therapeutic candidates is one of the key challenges in medicinal chemistry. Podophyllotoxin and its derivatives, as a potent cytotoxic agent, have been at the center of extensive chemical amendment and pharmacological investigation. Herein, a new series of podophyllotoxin-N-sulfonyl amidine hybrids (4a–4v, 5a–5f) were synthesized by a CuAAC/ring-opening procedure. All the synthesized podophyllotoxins derivatives were evaluated for in vitro cytotoxic activity against a panel of human lung (A-549) cancer cell lines. Different substituents’, or functional groups’ antiproliferative activities were discussed. The –CF3 group performed best (IC50: 1.65 μM) and exhibited more potent activity than etoposide. Furthermore, molecular docking and dynamics studies were also conducted for active compounds and the results were in good agreement with the observed IC50 values.